ANALISIS PENGARUH CUSTOMER SERVICE EXPERIENCE TERHADAP BEHAVIOR INTENTIONS (Survei pada Wisatawan Sebagai Tamu Individu yang Menginap di Sheraton Mustika Yogyakarta Resort and Spa) - Syahid, Kendid; Andari, Rini; Abdullah, Taufik (Universitas Pendidikan Indonesia, 2014)
Sheraton Mustika Yogyakarta Resort and Spa strive to provide good service to the‘’in touch’’ service oriented so that guests experience a memorable service. In order to get the guests who willing to stay longer, recommending and repurchasing, then Sheraton Mustika Yogyakarta conduct stratergi namely Star Customer Experience. The purpose of this research is to describe the customer service experience as the independent variable (X), describe of behavior intentions as the dependent variable (Y) and analyze the effect of customer service experience towards behavior intentions. The method used in this research is descriptive and verification due to this research is conducted less than one year so this research is a cross-sectional method. The sampling technique used is systematic random sampling with a sample of 100 first-timer guests. The data analysis technique used is multiple regression. The results showed that the highest score in customer service experience is the sub-variables for the assessment of empathy while the lowest is recognition. The highest valuation for the variables dimensions of behavior intentions is repurchasing intention while dimension of willingness to recommend is the lowest. Simultaneously customer service experience significantly influence on behavior intentions.